2012
DOI: 10.5021/ad.2012.24.1.61
|View full text |Cite
|
Sign up to set email alerts
|

Association betweenIL17A/IL17RAGene Polymorphisms and Susceptibility to Alopecia Areata in the Korean Population

Abstract: BackgroundAlopecia areata is marked by autoimmune assault on the hair follicle resulting in hair loss. T helper 17 cell subset has important roles in protecting the host against extracellular pathogens, however, also promotes inflammatory pathology in autoimmune disease, and it expresses both interleukin (IL)-17A and IL-17F, which can signal via the IL-17 receptor A.ObjectiveTo investigate the significance of IL17A and IL17RA gene polymorphisms in the susceptibility to alopecia areata.MethodsWe conducted case-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
52
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 66 publications
(59 citation statements)
references
References 26 publications
3
52
0
Order By: Relevance
“…IL-23, a cytokine produced by dendritic cells and other antigen-presenting cells, serves as a pivotal factor that drives both the differentiation and inflammatory functions of pathogenic T H 17 cells [97]. It has been revealed that SNPs of the IL17RA gene are associated with AA onset age in Korean patients [98]. Serum cytokine levels of IL-17A are significantly increased, and TGFβ1 is significantly decreased, in patients with AA compared with controls [99].…”
Section: Th17 Cells May Contribute To Alopecia Areata Developmentmentioning
confidence: 99%
“…IL-23, a cytokine produced by dendritic cells and other antigen-presenting cells, serves as a pivotal factor that drives both the differentiation and inflammatory functions of pathogenic T H 17 cells [97]. It has been revealed that SNPs of the IL17RA gene are associated with AA onset age in Korean patients [98]. Serum cytokine levels of IL-17A are significantly increased, and TGFβ1 is significantly decreased, in patients with AA compared with controls [99].…”
Section: Th17 Cells May Contribute To Alopecia Areata Developmentmentioning
confidence: 99%
“…Among them, T helper 17 cells, characterized by interleukin-17 (IL-17) production, play a critical role in the pathogenesis of autoimmune disease [5]. Interestingly, Lew et al [6] recently reported an association between IL17RA gene polymorphism and AA. In this report, we performed a quantitative analysis of IL-17-producing cells in the lesional skin of several clinical types of AA (multiple patchy types, totalis types and ADTA).…”
Section: Introductionmentioning
confidence: 99%
“…Lew et al conducted a case-control association study of 238 AA patients, in which, IL17A and IL17RA (IL-17A receptor) gene polymorphisms were detected [100].…”
Section: Secukinumabmentioning
confidence: 99%